FUNCTIONAL MOVEMENT SCREENING : DETEKSI DINI RISIKO CEDERA OLAHRAGA ATLET PANJAT TEBING KOTA PADANG - Adea Oktarisa; Donal Syafrianto; Pudia M Indika; Yogi Andria (Jurnal IKEOR, 2023)
: Injuries are common in rock climbing, both during training and competition. A system called Functional Movement Screening (FMS) is used to assess the risk of sports injuries. The Functional Movement screening (FMS) is a quantitative assessment tool for determining the functional mobility of the human body. This study aims to determine the level of risk of sports injury in rock climbing athletes in Padang City using the FMS method. This study used a quantitative descriptive method with a cross-sectional approach. The sample in this study were rock climbing athletes in the city of Padang with a total of 10 people who were taken using the total side technique. The FMS test, which consisted of seven movements, was used as the research instrument. Based on the results of the Functional Movement Screening (FMS) test, rock climbing athletes in Padang City were identified as having a high risk of injury. As a result, there is no balance of strength between the right and left body muscles. In addition, the results of the study also show that when viewed from the intrinsic ability in terms of mobility and functional patterning of rock climbing athletes in Padang City, it is quite good, but in the intrinsic aspect of motor control, it seems that it is still not good.